Flight Control System Simulation Platform for UAV Based on Integrating Simulink With Stateflow - Gao Yanhui; Xiao Qiangui; Hu Shousong; Ju Xiao (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Aiming at rapidly analyzing and validating control strategy, control law and flight mode of the Unmanned Aerial Vehicle (UAV), a digital simulation test platform for flight control system (FCS) of UAV is presented in this paper. The platform is built on principles of hierarchy and modularity, its core is composed of flight mode management and control module, and the two components are implemented by using Matlab/Stateflow and embedded Simulink Function respectively. Simulation test for a certain type of UAV with a variety of flight mode, including remote control and autonomic flight, is achieved. Compared with actual flight test, the results of the simulation validate the rationality and validity of the modeling theories and method. Practices show that developing new type or modified FCS of UAV through this platform, similarity between simulation model and real aircraft can be improved, and this is useful to minimize the risk and increase flexibility for design changes. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1345